PENGARUH LITERASI KEUANGAN, PERSEPSI KEMUDAHAN PENGGUNAAN, KEAMANAN DAN SELF EFFICACY TERHADAP MINAT MENGGUNAKAN MOBILE BANKING WONDR BNI PADA GEN Z SURABAYA - Pradana, Naufall Makarim Nurman; Pertiwi, Tri Kartika (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of financial literacy, perceived ease of use, security, and self-efficacy on the interest of Generation Z in Surabaya in using Wondr BNI mobile banking. The background of this study is based on ai the low adoption rate of Wondr BNI even though Gen Z is a group of digital natives who are active in using digital financial services. The research method used is quantitative with purposive sampling technique. The research sample consisted of 120 respondents, consisting of Gen Z residing in the city of Surabaya. Data analysis was conducted using (PLS-SEM) through the SmartPLS 4.The results show that financial literacy does not have a significant effect on interest in use, indicating that the adoption of mobile banking no longer requires a deep understanding of finance. Instead, perceptions of ease of use, security, and self-efficacy were found to have a positive and significant effect on interest in use.